дидактические материалы решебник алгебра 7 класс Звавич

Вариант 2

с-7

1. 1) a) 3,4 • 5c = 17c
6) -4,5c • 8 = -36c
в) 0,7 • 3,8c = 2,66c
г) -5a • (-12) = 60a
2) a) -6х • 1,25y = -7,5xy
б) 7,5а • 2х = 15аx
в) -0,6b • 4y = -2,4by
г) 5/11p • 11/20q = 1/4pq.

2. 1) a) 5b + 7b = 12b
6) 6x - 13x = -7x
в) -5a - 8a = -13a
г) -3,4y + 8y = 4,6y
д) -5,4х + х = -4,4х
е) -c - 0,2c = -1,2c
ж) 1/5x - 3x = -2,8x
з) 1/3a + 1/4a = 7/12a
и) 5/7b - b = -2/7b
2) a) 9a + 17a - 30a + 4a = a(9 + 17 - 30 + 4) = 0
6) -5x + 11x + 47x - 31x = 22x
в) -k - k - 5а - а - а - а = -2k - 8a
г) 5,17y + 9,31y + 4,83y - 2y = 17,31y
3) a) 15a - a + b - 6b = 14a - 5b
б) -12c - 12a + 7a + 6c = -6c - 5a
в) 1,7x - 1,2y - 1,7x + 0,5y = -0,7y
г) 7 - x + y + x - y = 7
д) 3a - a - b - 12b - 7 = 2a - 13b - 7
е) 1,8y + 3 - 2,8c - 0,2 - 2y = -0,2y - 2,8c + 2,8.

3. 1) а) k + (m + n) = k + m + n; в) -k - (m - n) = -k - m + n;
6) k - (m + n) = k - m - n;            г) k -(-m - n) = k + m + n;
2) a) (x - y) + (a + b) = x - y + a + b
6) ( a- c) - (b - d) = a - c - b + d
в) -a + (b - c) - (x - y) = -a + b - с - x + у
г) 25 - (m - n) - (a - b) = 25 - m + n - a + b

4. 1) а) 2а + (3а - 8b) = 2а + 3а - 8b = 5a - 8b
б) -5b - (8a - 5b) = -5b - 8a + 5b = -8a
в) 6x + (7 - 3x) = 6x + 7 - 3x = 3х + 7
г) -(4х - 18) + 18 = -4x + 18 + 18= -4x + 36
2) a) (5 - 2b) - (7 + 10b) = 5 - 2b - 7 - 10b = -2 - 12b
б) -(3c + 5x) - (9c - 6x) = -3c - 5x - 9c + 6x = 12c + x
в) (2a - 7y) - (5a - 7y) = 2a - 7y - 5a + 7y = -3a
г) (11p + 9c) - (12 + 11p + 9c) = 11p + 9c - 12 - 11p - 9c = -12
3) a) x - (x - 15) + (13 + x) = x - x + 15 + 13 + х = 28 + x
б) (3а - 21) - 2а - (17 - 8a) = 3а - 21 - 2а - 17 + 8a = 9a - 38
в) (2 - 4b) - (31b - b) - 11 = 2 - 4b - 31b + 6 - 11 = -35b - 3
г) 14b - (15b + y) - (у + 10b) = 14b - 15b - y - y - 10b = -11b - 2y.

5. 1) а) 7(5a + 8) - 11а = 35а + 56 - 11a = 24а + 56
б) 9x + 3(15 - 8x) = 9x + 45 - 24x = -15x + 45
в) 6(с + 1) - 6с - 5 = 6с + 6 - 6с - 5 = 1
г) 19у + 2(3 - 4у) + 11у = 19у + 6 - 8у + 11у = 22у + 6
2) а) 13a - 8(7a - 1) = 13а - 56a + 8 = -43a + 8
б) -2(2р - 1) + 4 = -4р + 2 + 4 = -4р + 6
в) 21х - 7 - 4(9x + 3) = 21х - 7 - 36х - 12 = -15х - 19
г) 33 - 8(11b - 1) - 2b = 33 - 88b + 8 - 2b = -90b + 41.

6. а) x - (x - (3x - 1)) = x - x + (3x - 1) = 3x - 1
б) 12y - ((x - y) + 12х) = 12у - (х - у) - 12x = 12у - х + у - 12x = 13y - 13x
в) 5а - (6а - (7а - (8а - 9))) = 5а - 6а + 7а - 8а + 9 = -2а + 9
г) 13b - (9b -((с - b) - 9b)) = 13b - 9b + с - b - 9b = -6b + с

7. а) 0,7b + 0,3b - 1,5 = b - 1,5; -0,81 - 1,5 = -2,31
б) 1,7а - 18,7 - 16,3 = 1,7а - 35; 1,7 • 3,8 - 35 = -28,54
в) 2,4x - 8,4 - 2х + 0,4 = 0,4x - 8; 2/5 • 25/6 - 8 = -19/3
г) 36/7y - 36 - 64 + 32/7y = 68/7y - 100;
-68/7 • 3/10 - 100 = -102/35 - 100 = (-102-3500)/35 = -102 32/35.